Analisis Kedudukan Anak Angkat dalam Pembagian Warisan Ditinjau dari Hukum Adat Karo: Studi di Desa Dokan Kecamatan Merek Kabupaten Karo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the legal status of adopted children in inheritance distribution according to Karo customary law. The method used is qualitative research with an empirical juridical approach. This approach was chosen to explore the interaction between customary legal norms and practices that occur in Karo society. Through an empirical approach, researchers seek to directly understand how inheritance distribution is carried out in the daily lives of the Karo customary community. The research data sources consist of primary data obtained through direct interviews with traditional leaders, field observations, and documentation, while secondary data comes from literature, regulations, and related documents. Data analysis was conducted qualitatively with the stages of data reduction, data presentation, and verification or drawing conclusions. The results of the study indicate that the Karo community, particularly in Dokan Village, recognizes that adopted children adopted through the Perkahkah Bohan traditional ritual have equal status to biological children in social and emotional aspects. Adopted children who are adopted before a married couple has biological children usually receive full inheritance rights, especially if the child is male. However, if the adopted child arrives after the birth of a biological child, the inheritance rights received tend to be smaller or different, which are determined based on family deliberation. The factor of customary legitimacy through traditional rituals plays a crucial role in determining the status of adopted children regarding inheritance rights. These findings confirm that Karo customary law is dynamic, adapting to social conditions while maintaining the principle of patrilineal kinship as the primary basis of the inheritance system. Thus, the status of adopted children in Karo customary law is not static, but rather contextual, in accordance with customary values and collective family decisions.